POLONG PALING SEDIKIT PADA GALUR KACANG HIJAU (Vigna radiata (L.) Wilczek) LOKAL KAMPAR - Desnilia '; Herman '; Dewi Indriyani Roslim (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The mungbean demand in the market increases but it is difficult to provide the stock because mungbean production is low due to low interest of local people to cultivate thisspecies. Riau Province has common mungbean strain, i.e. Kampar local strain that has low fruit production, unsimultaneous ripe physiological characters, and trichomes. One of the effort of plant breeding use of strain purification. The purpose of this study was to identify the second generation of local mungbean strain from Kampar that has thelowest number of pods. The experiment was conducted from April to June 2013 in the gardens of Biology, Faculty of Math and Natural Science, University of Riau using a completely randomized design. Eight strains were examined with five replications in each strain. The observed character was number of pod. Data was analyzed using SPSS 16.0. The results showed that mungbeans strains (G1, G2, G3, G4, and G6) had thelowest number of pods.